Cell Salvage Use, Benefits, and Costs at Ipswich Hospital Spinal Unit UK. Issue 1 (April 2016) - Marjoram, Tom; Kaleel, Saajid; Cumming, David; Lovell, Robert; Bhagat, Shaishav; Hudd, Alisair; Sharp, David; Powell, John
Introduction: Blood Transfusions cost £122 per unit in the UK but they have other costs including 1:13000 incorrectly transfused. 1:7000 risk of adverse reaction. Infection in the UK overall is 1:1.2milliion for hepatitis B and 1:7million for HIV with a risk of 1:28million for hepatitis C. Methods: We analyzed the use of cell saver and blood transfusion in the Ipswich Spinal Unit (UK). Identifying all cases in which cell saver might be used. Looking at the volume collected and re-infused to the patient, the pre- and post operative haemoglobin and the need for blood transfusion Results: We found that Cell saver was being used for a variety of cases including Trauma, Revision surgery, Deformity Correction, Anterior Lumbar fusions, Trans-laminar interbody fusions and tumor work. Revision surgery alone did not have a significant need for blood transfusion and cell saver use in these cases was often (66%) of the time not required. ALIF surgery only utilized salvaged blood in 10% of cases but the bleeding in this case was significant and therefore the unit decided cell salvage would continue to be routine. Overall we found that the average drop in haemoglobin was comparable between those patients who had cell salvage technology utilized during their surgery compared with those who did not, this was echoed in the post operative blood transfusion rates. A cost analysis based upon the cost of cell salvage use vs the cost that would have theoretically been incurred if the same volume of donated blood had been used showed cell salvage to cost 43% more that the use of donated blood products. Conclusion: Cell salvage is a more financially costly technology than transfusion from the blood bank. There are some procedures in which the routine use of cell salvage should be reserved for specific cases and some where the use in a small percentage is so beneficial that cell salvage will continue to be used despite a low overall re-infusion rate. The additional costs to the patients is to be considered when discussion donated blood transfusion. The Ipswich Spinal Unit believes more judicious use of cell salvage technology concentrating on the cases in which we found utilization to be highest would make it more cost effective.